Emerging concepts in high-impact publishing: insights from the First Brazilian Colloquium on High Impact Research and Publishing - Valerie Matarese
Reports of scientific research are published by selective journals only when they meet stringent criteria, first and foremost of which are the quality and importance of the research. Even when the research is excellent, other elements come into play to determine if the manuscript will be accepted for publication. Many of these factors are under direct control of the researcher-author, but not all authors are aware of the elements of high-impact scientific writing. At the First Brazilian Colloquium on High Impact Research and Publishing, editors of leading biomedical journals provided insight on the aspects of scientific reporting that favor acceptance (or immediate rejection). This commentary summarizes the editors' advice and uses the debate that followed as the basis for analyzing emerging concepts in high-impact publishing. Lessons learned from this meeting are relevant to researcher-authors in other non-anglophone countries as well as to their educators and administrators who wish to improve the impact of the research that they support and finance.